The Effect Of Training And Work Motivation On The Performance Of Village Office Employees In Seginim District, South Bengkulu Regency - Mardhiyah Dwi Ilhami; Taufik Bustam; Gegen Prasetyo (Penerbit Jurnal Indonesia, 2023)
This study aims to determine